Číst, pochopit, interpretovat. Literární prozaický text ve výuce cizího jazyka a ve výuce literatury - Andrea Králíková — Jana Marková; Jana Marková (Slovo a Smysl, 2023)
In this study, based on observations of our own pedagogical work, we consider different didactic approaches to the same literary text (the short story ‘From Prague to Brno’ by Jiří Kratochvil) in the teaching of Czech as a foreign language and in the teaching of literature, including analysis of literary texts. The starting point is a comparison of the learning objectives in both of these contexts, followed by a presentation of specific tasks and lines of inquiry vis-à-vis the text, their justification, and analysis of student reactions. In conclusion, we emphasize those aspects that should be considered in the teaching of literary and prose texts, not only by foreign language teachers but also (in our view) teachers of literature and literary interpretation.